A distinct LHCI arrangement is recruited to photosystem I in Fe-starved green algae - Helen W. Liu; Radhika Khera; Patricia Grob; Sean D. Gallaher; Samuel O. Purvine; Carrie D. Nicora; Mary S. Lipton; Krishna K. Niyogi; Eva Nogales; Masakazu Iwai; Sabeeha S. Merchant (Proceedings of the National Academy of Sciences, 2025)
Iron (Fe) availability limits photosynthesis at a global scale where Fe-rich photosystem (PS) I abundance is drastically reduced in Fe-poor environments. We used single-particle cryoelectron microscopy to reveal a unique Fe starvation-dependent arrangement of light-harvesting chlorophyll (LHC) proteins where Fe starvation–induced TIDI1 is found in an additional tetramer of LHC proteins associated with PSI in Dunaliella tertiolecta and Dunaliella salina . These cosmopolitan green algae are resilient to poor Fe nutrition. TIDI1 is a distinct LHC protein that co-occurs in diverse algae with flavodoxin (an Fe-independent replacement for the Fe-containing ferredoxin). The antenna expansion in eukaryotic algae we describe here is reminiscent of the iron-starvation induced ( isiA- encoding) antenna ring in cyanobacteria, which typically co-occurs with isiB , encoding flavodoxin. Our work showcases the convergent strategies that evolved after the Great Oxidation Event to maintain PSI capacity.